2013
DOI: 10.1007/s13760-013-0239-x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and their pathological upregulation in multiple sclerosis: an overview

Abstract: Matrix metalloproteinases (MMPs) are a family of extracellular proteases associated with extracellular matrix remodeling. They are involved in many physiological and reparative processes. MMPs can break down all extracellular constituents; therefore, their expression is very tightly regulated and their abnormal activity or over production has been linked to many diseases including multiple sclerosis (MS) which is a leading cause of non-traumatic disability in young adults in North America. Recently many studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…The second mechanism is activation of inactive forms of certain inflammation mediators by increased levels of MMPs. Breakdown of the myelin sheath within the CNS parenchyma by MMPs results in demyelination and inflammation within the CNS (19). The release of MMPs at the sites of inflammation and their role in degradation of the various components of the extracellular matrix (19,20) indicates that the genetic variants of MMPs might affect the function of MMP enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The second mechanism is activation of inactive forms of certain inflammation mediators by increased levels of MMPs. Breakdown of the myelin sheath within the CNS parenchyma by MMPs results in demyelination and inflammation within the CNS (19). The release of MMPs at the sites of inflammation and their role in degradation of the various components of the extracellular matrix (19,20) indicates that the genetic variants of MMPs might affect the function of MMP enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, the majority of remaining MMP activity is isolated to remodeling processes such as wound repair and angiogenesis. However, in human disease, aberrant MMP hyperactivity has been observed in many pathological conditions, such as osteoarthritis, multiple sclerosis, and cancer 2,42…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…Matrix metalloproteinases (MMP) constitute a large group of proteolytic enzymes involved in degrading and remodeling the extracellular matrix. In order to alter the extracellular matrix, MMP must modify (activate or inactivate) a variety of soluble or membrane‐bound proteins, which can occur in normal physiological and pathological conditions, such as multiple sclerosis and atherosclerosis . It has been shown that different cell types, such as lymphocytes, macrophages and glial cells, produce MMP, and these enzymes play important roles in the pathogenesis of inflammatory diseases of the central nervous system (CNS) .…”
Section: Introductionmentioning
confidence: 99%
“…In order to alter the extracellular matrix, MMP must modify (activate or inactivate) a variety of soluble or membrane-bound proteins, which can occur in normal physiological and pathological conditions, such as multiple sclerosis and atherosclerosis. [1][2][3][4] It has been shown that different cell types, such as lymphocytes, macrophages and glial cells, produce MMP, and these enzymes play important roles in the pathogenesis of inflammatory diseases of the central nervous system (CNS). [1][2][3][4] For example, in multiple sclerosis (MS), MMP might contribute to the migration of immune cells into the CNS from the bloodstream through proteolytic disruption of the subendothelial basement membrane of the blood-brain barrier (BBB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation